Methacrylic resin composition for multicolor molding, and multicolor molding

Through specific methylpropionate resin combination and rheological characteristic control, the color transfer problem in the multi-color injection molded body is solved, and a multi-color molded body with high design and good appearance is achieved.

JP2025051757APending Publication Date: 2025-04-04ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024164349
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-22
Filing Date
2024-09-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, when using methyl propionate resin as the surface material and polycarbonate (PC), ABS resin or PC/ABS resin as the base material, color transfer problems are serious, affecting the appearance of the product.

Method used

A specific combination of methylpropionate resins is used to perform vibration frequency sweep tests through a rotary rheometer to control the rheology characteristics and glass transition temperature to suppress color transfer and maintain a good appearance.

Benefits of technology

It effectively inhibits color transfer, maintains the high designability and appearance quality of multi-color molded bodies, and is suitable for automotive parts and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025051757000001_ABST
    Figure 2025051757000001_ABST
Patent Text Reader

Abstract

To provide a methacrylic resin composition which can be formed into a multicolor molding without impairing high designability, and a multicolor molding which is composed of a methacrylic resin composition.SOLUTION: A methacrylic resin composition for multicolor molding has shear viscosity using a cone plate jig, at a distance between gaps of 0.05 mm, a strain of 10%, under a nitrogen gas stream, at 260°C, and at angular velocity of 1 rad / sec of 1,800 pascal seconds or more and 5,000 pascal seconds or less, shear viscosity at angular velocity of 100 rad / sec of 300 pascal seconds or more and 1,000 pascal seconds or less, and a Vicat softening temperature measured according to ISO 306 B50 of 104°C or higher and 140°C or lower.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a methacrylic resin composition for multicolor molding and a multicolor molded article. [Background technology]

[0002] Methacrylic resin compositions are characterized by having high light transmittance, weather resistance, rigidity, etc. as transparent resins compared to other plastic transparent resins, and have been used in a wide range of applications, such as electrical and electronic components, battery components, vehicle components, lighting fixtures, building materials, signs, nameplates, paintings, display device windows, etc. Among these, methacrylic resin compositions are widely used as electrical and electronic components, vehicle parts, and lighting fixtures due to their glossy color tone, high light transmittance, high appearance, and good weather resistance when used as a coloring material.

[0003] In recent years, there has been a demand for higher design than ever before, and the use of multi-color molded articles in which molded articles made of resin compositions of various colors are integrated into one body is increasing. There is particularly strong demand for multi-color molded articles as automotive components, and various studies are being conducted to meet such demands. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-202537 A [Patent Document 2] JP 2019-202538 A Summary of the Invention [Problem to be solved by the invention]

[0005] For example, Patent Documents 1 and 2 disclose two-color injection molded products having a surface layer of methacrylic resin and a base layer of polycarbonate resin (PC), ABS resin (acrylonitrile, butadiene-styrene copolymer), or PC / ABS resin. However, the methacrylic resin and two-color injection molded products disclosed in Patent Document 1 have a problem that when a two-color molded product having a heat-welded portion is formed from a molded product made of a highly transparent methacrylic resin composition having a total light transmittance of 80% or more and a molded product made of a colored methacrylic resin composition having a total light transmittance of 50% or less, remelt occurs, and the color of the molded product made of the colored methacrylic resin composition transfers to the molded product made of the highly transparent methacrylic resin composition, impairing the appearance.

[0006] Therefore, there has been a strong demand for a methacrylic resin composition that can be made into a multicolor molded article without impairing high designability, and a multicolor molded article made of a methacrylic resin composition. [Means for solving the problem]

[0007] Means for Solving the Problems of the Prior Art The present inventors have conducted intensive research into materials used for multicolor molded articles in order to solve the problems of the prior art described above. As a result, they have discovered that by using a specific methacrylic resin composition, color transfer is suppressed and a good appearance is achieved when the article is used as a multicolor molded article, and have thus completed the present invention.

[0008] That is, the present invention is as follows. [1] Using a rotational rheometer, the oscillation frequency sweep test mode was performed with a cone-plate fixture, with a gap of 0.05 mm and a strain of 10%, under a nitrogen gas flow, at a test temperature of 260°C, with a shear viscosity of 1800 Pascal-seconds to 5000 Pascal-seconds at an angular velocity of 1 rad / second, and a shear viscosity of 300 Pascal-seconds to 1000 Pascal-seconds at an angular velocity of 100 rad / second. The Vicat softening temperature measured in accordance with ISO 306 B50 is 104°C or higher and 140°C or lower. Methacrylic resin composition for multi-color molding. [2] The methacrylic resin composition for multicolor molding according to [1], having a midpoint glass transition temperature of 111°C or higher. [3] A multicolor molded article comprising the methacrylic resin composition for multicolor molding according to [1]. [4] A multi-color molded article having two or more colors made of a methacrylic resin composition, The present invention comprises a methacrylic resin composition molded product A having a total light transmittance of 80% or more, and a methacrylic resin composition molded product B having a total light transmittance of 50% or less, the methacrylic resin composition being a colored product for multicolor molding according to the above [1], The methacrylic resin composition molded body A and the methacrylic resin composition molded body B are at least partially heat-welded to each other. Multi-color moldings with two or more colors. [5] A multi-color molded article having two or more colors made of a methacrylic resin composition, The present invention comprises a methacrylic resin composition molded product A made of the methacrylic resin composition for multicolor molding according to [1] having a total light transmittance of 80% or more, and a colored methacrylic resin composition molded product B having a total light transmittance of 50% or less, The methacrylic resin composition molded body A and the methacrylic resin composition molded body B are at least partially heat-welded to each other. Multi-color moldings with two or more colors. [6] A multi-color molded article having two or more colors made of a methacrylic resin composition, The present invention comprises a methacrylic resin composition molded product A made of the methacrylic resin composition for multicolor molding according to [1] having a total light transmittance of 80% or more, and a colored methacrylic resin composition molded product B made of the colored methacrylic resin composition for multicolor molding according to [1] having a total light transmittance of 50% or less, The methacrylic resin composition molded body A and the methacrylic resin composition molded body B are at least partially heat-welded to each other. Multi-color moldings with two or more colors. [7] The multi-color molded article according to [4] or [5], wherein the molded article A made of the methacrylic resin composition and the molded article B made of the methacrylic resin composition are injection molded articles. [8] The multicolor molded product according to [4] or [5], wherein the heat-sealed portion accounts for more than 0% and not more than 60% of the surface area of ​​the design face of the multicolor molded product (100%). Effect of the Invention

[0009] According to the present inventors, it is possible to provide a methacrylic resin composition which, when used as a multicolor molded article, can suppress color transfer and exhibit a good appearance, and a multicolor molded article using the methacrylic resin composition. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a schematic diagram showing an example of a multicolor molded body according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment for carrying out the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the embodiment. In other words, the present invention can be modified in various ways without departing from the gist of the present invention.

[0012] In this specification, a structural unit constituting a polymer may be referred to as a "monomer unit" and / or a "structural unit" containing a plurality of such "monomer units." In addition, a material constituting the above-mentioned "monomer unit" may be referred to simply as a "monomer" without the word "unit."

[0013] <Methacrylic resin composition for multi-color molding> The methacrylic resin composition for multi-color molding of this embodiment has a shear viscosity of 1,800 Pascal-seconds or more and 5,000 Pascal-seconds or less and a shear viscosity of 300 Pascal-seconds or more and 1,000 Pascal-seconds or less at an angular velocity of 100 rad / second, measured using a rotational rheometer in an oscillation frequency sweep test mode using a cone-plate jig, with a gap of 0.05 mm, a strain of 10%, and a nitrogen flow at a test temperature of 260°C. The Vicat softening temperature measured in accordance with ISO 306 B50 is 104°C or more and 140°C or less.

[0014] The methacrylic resin composition of the present embodiment preferably contains 50% by mass or more of a methacrylic resin. The content of the methacrylic resin in 100% by mass of the methacrylic resin composition is preferably 85% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, from the viewpoint of expressing the excellent weather resistance, high transparency, and color development when colored that the methacrylic resin has. In addition, the content of the methacrylic resin is preferably 85 to 99.9% by mass, more preferably 90 to 99.8% by mass, even more preferably 95 to 99.7% by mass, and particularly preferably 98% by mass or more and 99.7% by mass or less, in 100% by mass of the methacrylic resin composition of the present embodiment, in order to ensure visibility as a meter cover.

[0015] (Methacrylic resin) The methacrylic resin composition for multicolor molding of the present embodiment contains a methacrylic resin. The methacrylic resin is not particularly limited, but preferably contains 80 to 99.9 mass % of methacrylic acid ester monomer units and 0.1 to 20 mass % of vinyl monomer units composed of a vinyl monomer copolymerizable with the methacrylic acid ester monomer. The methacrylic resin may be a single methacrylic resin or a combination of two or more methacrylic resins.

[0016] Examples of the methacrylic acid ester monomer constituting the methacrylic acid ester monomer unit include, but are not limited to, butyl methacrylate, ethyl methacrylate, methyl methacrylate, propyl methacrylate, isopropyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, 2-ethylhexyl methacrylate, t-butylcyclohexyl methacrylate, benzyl methacrylate, 2,2,2-trifluoroethyl methacrylate, etc. Among these, it is preferable to use methyl methacrylate and ethyl methacrylate from the viewpoints of availability and price. The above methacrylic acid ester monomers may be used alone or in combination of two or more.

[0017] The content of the methacrylic acid ester monomer unit is preferably 80 to 99.9% by mass, more preferably 93 to 99.8% by mass, even more preferably 95 to 99.5% by mass, and particularly preferably 96 to 99.5% by mass, based on 100% by mass of the methacrylic resin. By making the content of the methacrylic acid ester monomer unit 99.9% by mass or less, decomposition of the resin during molding can be prevented, and the generation of the methacrylic acid ester monomer, which is a volatile component, and molding defects called silver can be effectively prevented. In addition, by making the content of the methacrylic acid ester monomer unit 80% by mass or more, the heat resistance generally required for molded products can be ensured. By having sufficient heat resistance, rigidity can also be ensured, and the strength generally required for molded products can be ensured.

[0018] Examples of vinyl monomers copolymerizable with the methacrylic acid ester monomers include, but are not limited to, acrylic acid ester monomers having one acrylate group, such as methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, and 2-ethylhexyl acrylate. Other examples of the acrylic acid ester monomer include those in which both terminal hydroxyl groups of ethylene glycol or its oligomers having two or more (meth)acrylate groups are esterified with acrylic acid or methacrylic acid, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate; those in which hydroxyl groups of two alcohols, such as neopentyl glycol di(meth)acrylate and di(meth)acrylate, are esterified with acrylic acid or methacrylic acid; and those in which polyhydric alcohol derivatives, such as trimethylolpropane and pentaerythritol, are esterified with acrylic acid or methacrylic acid. Among these, the vinyl monomer copolymerizable with the methacrylic acid ester monomer is preferably methyl acrylate, ethyl acrylate, or n-butyl acrylate, more preferably methyl acrylate or ethyl acrylate from the viewpoint of availability, and particularly preferably methyl acrylate from the viewpoint of copolymerizability. These may be used alone or in combination of two or more. In this specification, a methacrylic acid ester refers to a compound having only one methacrylate group, and a methacrylic acid ester having a plurality of methacrylate groups is regarded as another monomer copolymerizable with the methacrylic acid ester.

[0019] The content of the vinyl monomer unit consisting of a vinyl monomer copolymerizable with the methacrylic acid ester monomer is preferably 0.1 to 20 mass%, more preferably 0.2 to 7 mass%, further preferably 0.5 to 5 mass%, and particularly preferably 0.5 to 4 mass%, based on 100 mass% of the methacrylic resin. By making the content 0.1 mass% or more, decomposition of the resin during molding can be prevented, and the generation of the methacrylic acid ester monomer, which is a volatile component, and molding defects called silver can be effectively prevented. In addition, by making the vinyl monomer unit 20 mass% or less, the heat resistance generally required for molded products can be ensured. In addition, the content of the vinyl monomer unit is preferably 0.2% by mass or less, particularly when a monomer having two (meth)acrylate groups is used, 0.1% by mass or less, when a monomer having three (meth)acrylate groups is used, and 0.03% by mass or less, when a monomer having four or more (meth)acrylate groups is used, relative to the methacrylic resin (100% by mass), from the viewpoint of ensuring fluidity during injection molding and maintaining transparency.

[0020] Examples of vinyl monomers other than the acrylic acid ester monomers that can be copolymerized with the methacrylic acid ester monomers include, but are not limited to, α,β-unsaturated acids such as acrylic acid and methacrylic acid; unsaturated group-containing divalent carboxylic acids and their alkyl esters such as maleic acid, fumaric acid, itaconic acid, and cinnamic acid; styrene monomers such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, and isopropenylbenzene (α-methylstyrene); 1-vinylnaphthalene aromatic vinyl compounds such as acrylonitrile, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, and isopropenyloctylbenzene; vinyl cyanide compounds such as acrylonitrile and methacrylonitrile; unsaturated carboxylic acid anhydrides such as maleic anhydride and itaconic anhydride; maleimide, and N-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide; amides such as acrylamide and methacrylamide; and polyfunctional monomers such as divinylbenzene. Among these, for the purpose of improving heat deformation resistance, structural units derived from N-substituted maleimides such as N-phenylmaleimide and N-cyclohexylmaleimide, and unsaturated carboxylic anhydrides such as maleic anhydride, as vinyl monomers other than the above-mentioned acrylic acid ester monomers, are preferably contained in an amount of 1% by mass or more and 20% by mass or less, more preferably 1% by mass or more and 12% by mass or less, and even more preferably 1% by mass or more and 6% by mass or less, relative to 100% by mass of the methacrylic resin.

[0021] In the above methacrylic resin, a vinyl monomer other than the above-mentioned vinyl monomers may be appropriately added and copolymerized for the purpose of improving properties such as heat resistance and moldability. The acrylic acid ester monomer copolymerizable with the methacrylic acid ester monomer and the vinyl-based monomer other than the acrylic acid ester monomers exemplified above may be used alone or in combination of two or more kinds.

[0022] Next, the weight average molecular weight (Mw) of the methacrylic resin contained in the methacrylic resin composition of this embodiment will be described. The above-mentioned methacrylic resin preferably has a weight average molecular weight (Mw) measured by GPC (gel permeation chromatography) of 80,000 or more to obtain excellent mechanical strength and solvent resistance to alcohol-based disinfectants and gasoline, and 180,000 or less to exhibit good fluidity during molding. In order to obtain excellent mechanical strength and solvent resistance to alcohol-based disinfectants and gasoline, the lower limit of the weight average molecular weight (Mw) of the methacrylic resin is preferably 85,000 or more, more preferably 92,000 or more, even more preferably 95,000 or more, even more preferably 97,000 or more, and particularly preferably 98,500 or more. In order for the methacrylic resin composition to exhibit good fluidity required for injection molding, the upper limit of the weight average molecular weight (Mw) of the methacrylic resin is preferably 165,000 or less, more preferably 155,000 or less, even more preferably 148,000 or less, and particularly preferably 144,000 or less. By setting the weight average molecular weight (Mw) of the methacrylic resin within the range of 80,000 to 180,000, it is possible to achieve a good balance between flowability, mechanical strength, and solvent resistance during molding, and good molding processability is maintained. Mw can be adjusted by the method described below.

[0023] The molecular weight distribution (Mw / Mn) of the methacrylic resin is preferably 1.5 to 6.0, more preferably 1.7 to 5.5, and even more preferably 2.3 to 4.0. When the molecular weight distribution (Mw / Mn) of the methacrylic resin is 1.5 or more, good fluidity is exhibited, and when it is 6.0 or less, the physical properties exhibited by the methacrylic resin are stable. Here, Mw represents the weight average molecular weight, and Mn represents the number average molecular weight. Mw / Mn can be adjusted by melt-kneading two or more types of polymers or adding a molecular weight regulator during polymerization. The weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin can be measured by GPC, for example, by the method described in the Examples below. Specifically, a calibration curve is created from the elution time and weight average molecular weight using a standard methacrylic resin with a known monodisperse weight average molecular weight and available as a reagent, and an analytical gel column that elutes high molecular weight components first. Based on the calibration curve obtained, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin to be measured can be obtained, and the molecular weight distribution (Mw / Mn) can be calculated from these. The number average molecular weight (Mn) is a simple average molecular weight per molecule, and is defined as the total weight of the system / the number of molecules in the system. The weight average molecular weight (Mw) is defined as the average molecular weight by weight fraction.

[0024] -Amount of molecular weight components less than 1 / 5 of the peak top molecular weight (Mp)- In order to improve moldability and impact resistance, the methacrylic resin preferably has an abundance of molecular weight components having a molecular weight of 1 / 5 or less of the peak top molecular weight (Mp) of 5 to 50%, more preferably 6 to 50%, even more preferably 7 to 45%, even more preferably 8 to 43%, and particularly preferably 10 to 30%. In particular, when the abundance of molecular weight components having a molecular weight of 1 / 5 or less of the peak top molecular weight (Mp) is 20 to 30%, the resin has an excellent balance of molding fluidity, melt shear viscosity, and impact resistance. Here, the abundance (%) of molecular weight components having a molecular weight of 1 / 5 or less of the peak top molecular weight (Mp) refers to the proportion of the area of ​​the area corresponding to molecular weight components having a molecular weight of 1 / 5 or less of the peak top molecular weight (Mp) when the total area of ​​the GPC elution curve is taken as 100%, and can be measured by the method described in the Examples below. The peak top molecular weight (Mp) refers to the weight molecular weight that shows a peak in a GPC elution curve. When a plurality of peaks are present in a GPC elution curve, the molecular weight of the peak that is the most abundant is taken as the peak top molecular weight (Mp). When the amount of molecular weight components present in the methacrylic resin that are 1 / 5 or less of the peak top molecular weight (Mp) is 6% or more, the light diffusing filler effectively prevents gas in the mold from being entrained during molding flow, causing an explosion and resulting in molding defects, thereby obtaining good moldability. Also, good molding flowability is obtained. When the amount is 50% or less, good impact resistance is obtained. Furthermore, the amount of methacrylic resin components having a molecular weight of 500 or less is preferably as small as possible in order to prevent the occurrence of foam-like appearance defects known as "silver" during molding.

[0025] -Mid-point glass transition temperature of methacrylic resins measured using a differential scanning calorimeter- The methacrylic resin preferably has a midpoint glass transition temperature (°C) of 109°C or higher, as determined from a glass transition curve obtained by heating from 40°C to 210°C at a heating rate of 10°C / min in a nitrogen gas atmosphere using a differential scanning calorimeter (DSC) and α-alumina as a reference in accordance with JIS K7121. The midpoint glass transition temperature (°C) obtained by the measurement method shown in the examples described later not only indicates that the higher the value, the better the heat distortion resistance of the resin, but also indicates the temperature at which the glass state transitions to a solid state, and the higher the value, the shorter the time from the molding temperature to solidification, which is effective in suppressing color migration and exhibiting good color migration resistance when forming a multi-color molded product. The above methacrylic resin preferably has a midpoint glass transition temperature of 109°C or higher, more preferably 110°C or higher, even more preferably 112°C or higher, and particularly preferably 113°C or higher. In addition, in order to achieve a good balance between the strength and fluidity of the methacrylic resin, the midpoint glass transition temperature is preferably 140°C or lower, more preferably 130°C or lower, even more preferably 120°C or lower, and particularly preferably 117°C or lower.

[0026] The methacrylic resin contained in the methacrylic resin composition of the present embodiment can be produced by, but is not limited to, a solution polymerization method, a bulk polymerization method, a cast polymerization method, or a suspension polymerization method. Preferred are the bulk polymerization method, the solution polymerization method, and the suspension polymerization method, and more preferred are the solution polymerization method and the suspension polymerization method from the viewpoint of heat removal.

[0027] The polymerization temperature of the methacrylic resin may be appropriately selected depending on the polymerization method, and in the suspension polymerization method, it is preferably from 50° C. to 100° C., more preferably from 60° C. to 90° C. In the solution polymerization method, it is preferably from 80° C. to 190° C., more preferably from 120° C. to 180° C.

[0028] When producing the methacrylic resin, a polymerization initiator may be used. The polymerization initiator is not limited to the following, but in the case of radical polymerization, for example, di-t-butyl peroxide, lauroyl peroxide, stearyl peroxide, benzoyl peroxide, t-butyl peroxy neodecanoate, t-butyl peroxy pivalate, dilauroyl peroxide, dicumyl peroxide, t-butyl peroxy-2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethyl peroxide, t-butyl peroxy-2-ethylhexanoate ... Examples of the radical polymerization initiator include organic peroxides such as t-butylcyclohexane and 1,1-bis(t-butylperoxy)cyclohexane, and general azo-based radical polymerization initiators such as azobisisobutyronitrile, azobisisovaleronitrile, 1,1-azobis(1-cyclohexanecarbonitrile), 2,2'-azobis-4-methoxy-2,4-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, and 2,2'-azobis-2-methylbutyronitrile. These initiators may be used alone or in combination of two or more. These radical polymerization initiators may be used in combination with a suitable reducing agent as a redox-based initiator. These radical polymerization initiators and / or redox initiators are generally used in an amount of more than 0 part by mass and not more than 1 part by mass per 100 parts by mass of the total amount of all monomers used in the polymerization of the above-mentioned methacrylic resin, and can be appropriately selected taking into consideration the temperature at which the polymerization is performed and the half-life of the polymerization initiator.

[0029] When bulk polymerization, cast polymerization, solution polymerization, or suspension polymerization is selected as the polymerization method for the methacrylic resin, it is preferable to carry out the polymerization using a peroxide polymerization initiator from the viewpoint of preventing coloration of the methacrylic resin. The peroxide polymerization initiator is not limited to the following, but examples thereof include lauroyl peroxide, decanoyl peroxide, and t-butylperoxy-2-ethylhexanoate, with t-butylperoxy-2-ethylhexanoate and lauroyl peroxide being more preferred.

[0030] When the above methacrylic resin is polymerized by a solution polymerization method at a high temperature of 90°C or higher, it is preferable to use as a polymerization initiator a peroxide, an azobis initiator, or the like, which has a 10-hour half-life temperature of 80°C or higher and is soluble in the organic solvent used. Examples of the peroxide and the azobis initiator include, but are not limited to, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, cyclohexane peroxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 1,1-azobis(1-cyclohexanecarbonitrile), and 2-(carbamoylazo)isobutyronitrile.

[0031] When producing the methacrylic resin, the molecular weight of the methacrylic resin may be controlled within the scope of the present invention. The method for controlling the molecular weight of the methacrylic resin is not limited to the following, but includes, for example, a method for controlling the molecular weight by using chain transfer agents such as alkyl mercaptans, dimethylacetamide, dimethylformamide, and triethylamine, and iniferters such as dithiocarbamates, triphenylmethylazobenzene, and tetraphenylethane derivatives. It is also possible to adjust the molecular weight by adjusting the amount of these additives.

[0032] As the chain transfer agent, from the viewpoint of handleability and stability, alkyl mercaptans are preferred. Examples of the alkyl mercaptans include, but are not limited to, n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, n-tetradecyl mercaptan, n-octadecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dithioglycolate, trimethylolpropane tris(thioglycolate), pentaerythritol tetrakis(thioglycolate), and the like.

[0033] The chain transfer agent and iniferter described above can be added appropriately depending on the molecular weight of the target methacrylic resin, but are generally used in the range of 0.001 to 5 parts by mass per 100 parts by mass of the total amount of all monomers used in the polymerization of the methacrylic resin.

[0034] Other molecular weight control methods include changing the polymerization method, adjusting the amounts of the polymerization initiator, the chain transfer agent, the iniferter, etc., and changing various polymerization conditions such as the polymerization temperature. These molecular weight control methods may be used alone or in combination of two or more.

[0035] <Ultraviolet absorbing agent> The methacrylic resin composition of the present embodiment preferably contains 0.005 to 0.5 parts by mass of an ultraviolet absorber relative to 100 parts by mass of the methacrylic resin. By containing an ultraviolet absorber, weather resistance is improved, and not only can a molded product suitable for long-term use be obtained when molded, but discoloration when exposed to light of a wavelength in the ultraviolet region contained in a light source can be effectively prevented. In order to fully exhibit the performance of the ultraviolet absorber, it is preferable that the ultraviolet absorber is contained in an amount of 0.005 parts by mass or more relative to 100 parts by mass of the methacrylic resin, more preferably 0.01 parts by mass or more, even more preferably 0.015 parts by mass or more, and particularly preferably 0.02 parts by mass or more. In addition, in order to prevent contamination of the mold and adhesion of the resin to the metal roll due to precipitation of the ultraviolet absorber during molding, it is preferable that the ultraviolet absorber is contained in an amount of 0.5 parts by mass or less relative to 100 parts by mass of the methacrylic resin, more preferably 0.3 parts by mass or less, even more preferably 0.2 parts by mass or less, and particularly preferably 0.1 parts by mass or less.

[0036] Examples of the ultraviolet absorber include, but are not limited to, benzotriazole-based compounds, benzotriazine-based compounds, benzoate-based compounds, benzophenone-based compounds, oxybenzophenone-based compounds, hindered amine-based compounds, phenol-based compounds, oxazole-based compounds, malonic acid ester-based compounds, cyanoacrylate-based compounds, lactone-based compounds, salicylic acid ester-based compounds, and benzoxazinone-based compounds, and are preferably benzotriazole-based compounds, benzotriazine-based compounds, and hindered amine-based compounds. The above ultraviolet absorbents may be used alone or in combination of two or more.

[0037] The vapor pressure (P) of the above ultraviolet absorber at 20°C is 1.0×10 -4 Pa or less, and more preferably 1.0×10 -6 Pa or less, and more preferably 1.0×10 -8 Pa or less.

[0038] Excellent moldability means, for example, that the ultraviolet absorbing agent adheres less to the surface of a mold during injection molding, or adheres less to a roll during extrusion molding. If the resin adheres to the roll, it may adhere to the surface of the molded article, thereby deteriorating the appearance and optical properties, which is not preferable when the molded article is used as an optical material.

[0039] <Dye and pigment> In the methacrylic resin composition of the present embodiment, the dye pigment (total mass of dye and pigment) is preferably contained in an amount of 0 to 2 mass% relative to 100 mass% of the methacrylic resin composition. When a transparent molded body made of the methacrylic resin composition is used as a molded body constituting a multicolor molded body, it is preferable not to use a dye pigment. On the other hand, when a colored molded body made of the methacrylic resin composition is used as a molded body constituting a multicolor molded body, it is preferable to use 0.0005 mass% or more and 1 mass% or less of the dye pigment. In order to obtain a color with good visibility, 0.001 mass% or more is more preferable, and 0.005 mass% or more is even more preferable. In the case of shading an internal light source, 0.1 mass% or more is more preferable, and 0.15 mass% or more is even more preferable. In addition, in order to prevent color transfer during the production of a multicolor molded body and to improve color transfer resistance, 0.8 mass% or less is more preferable, 0.4 mass% or less is even more preferable, 0.3 mass% or less is even more preferable, and 0.27 mass% or less is particularly preferable.

[0040] Examples of red dyes, as expressed by the Color Index, include Solvent Red 52, 111, 135, 145, 146, 149, 150, 151, 155, 179, 180, 181, 196, 197, 207, Disperse Red 22, 60, and 191. Examples of blue dyes, as expressed by the Color Index, include Solvent Blue 35, 45, 78, 83, 94, 97, 104, and 105. Examples of yellow dyes, as expressed by the Color Index, include Disperse Yellow 160, Disperse Yellow 54, 160, and Solvent Yellow 33. Examples of green dyes, as expressed by the Color Index, include Solvent Green 3, 20, and 28. Examples of purple dyes, as expressed by the Color Index, include Solvent Violet 28, 13, 31, 35, and 36. These dyes may be used alone or in combination of two or more for each color. The type of dye is not particularly limited, but from the viewpoint of weather resistance, dyes selected from the group consisting of anthraquinone dyes, heterocyclic compound dyes, and perinone dyes are preferred.

[0041] Examples of anthraquinone dyes, as expressed by the Color Index, include Solvent Violet 36, Solvent Green 3, 28, Solvent Blue 94, 97, and Disperse Red 22. Examples of heterocyclic compound dyes, as expressed by the Color Index, include Disperse Yellow 160. Examples of perinone dyes, as expressed by the Color Index, include Solvent Red 179 and Solvent Red 135. Each of these may be used alone or in combination of two or more.

[0042] In order to improve the resistance to color transfer, the melting point of the dye is preferably 190° C. or higher, more preferably 210° C. or higher, and even more preferably 220° C. or higher. In order to achieve good dispersibility in the resin, the melting point is preferably 350° C. or lower, more preferably 330° C. or lower, and even more preferably 300° C. or lower.

[0043] In order to further improve the color transfer resistance, the content of dyes having a melting point of less than 190°C is preferably 0 to 40 mass% or less, more preferably 0 to 37 mass% or less, even more preferably 0 to 20 mass% or less, and particularly preferably 0 mass% based on the total mass of the dyes.

[0044] Examples of pigments include, but are not limited to, iron oxide, titanium oxide, carbon black, barium sulfate, etc., and these may be included to obtain a desired color. In order to improve weather resistance and dispersibility, it is preferable to use a pigment whose surface is modified with a dispersant or a protective agent. In addition, the content of the dye or pigment in the present invention is the amount of pure pigment excluding surface treatment agents such as dispersants and protective agents. The amount of pigment added is preferably 0.005% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.02% by mass or more, based on 100% by mass of the methacrylic resin composition in order to achieve good color development and shielding properties when a colored molded product made of the methacrylic resin composition is obtained. Furthermore, in order to improve the impact resistance when a molded article made from the methacrylic resin composition is produced, the content is preferably 0.2% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0.05% by mass or less.

[0045] <Other additives> The methacrylic resin composition of the present embodiment may contain additives other than the above methacrylic resin, the above dye / pigment, and the above UV absorber, as long as the object of the present invention is not impaired. As the other additives, it is preferable to add a release agent, a heat stabilizer, other resins, and a strength modifier. The methacrylic resin composition of the present embodiment may be a composition consisting of only the methacrylic resin, the ultraviolet absorber, and the dye / pigment. The methacrylic resin composition of the present embodiment may be blended so that the total mass of the methacrylic resin, the ultraviolet absorber, the dye / pigment, and the other additives is 100% by mass.

[0046] (Heat stabilizer) Examples of the heat stabilizer include, but are not limited to, hindered phenol-based antioxidants and phosphorus-based processing stabilizers, with hindered phenol-based antioxidants being preferred.

[0047] Specifically, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide, 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert -butyl-4-hydroxy-m-tolyl)propionate, hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6 -xylin)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamine)phenol, and the like. Pentaerythritol terakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is a preferred heat stabilizer.

[0048] When using a heat stabilizer, in order to fully exert its effect, the amount of the heat stabilizer is preferably 0.03 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the methacrylic resin. In addition, in order to prevent mold contamination such as mold deposits, the amount of the heat stabilizer added is preferably 0.5 parts by mass or less, more preferably 0.4 parts by mass or less, and even more preferably 0.35 parts by mass or less.

[0049] (Other resins) The other resins used as the other components are not particularly limited as long as they do not impair the effects of the present invention, and known thermoplastic resins are preferably used. The other resins may be resins other than the methacrylic resins.

[0050] Examples of the thermoplastic resin include, but are not limited to, polypropylene resins, polyethylene resins, polystyrene resins, syndiotactic polystyrene resins, ABS resins (acrylonitrile-butadiene-styrene copolymers), AS resins (acrylonitrile-styrene copolymers), BAAS resins (butadiene-acrylonitrile-acrylonitrile rubber-styrene copolymers), AAS resins (acrylonitrile-acrylonitrile rubber-styrene copolymers), thermoplastic polyurethane resins, biodegradable resins, polycarbonate-ABS resin alloys, polyalkylene arylate resins such as polybutylene terephthalate, polyethylene terephthalate, polypropylene terephthalate, polytrimethylene terephthalate, and polyethylene naphthalate, polyamide resins, polyphenylene ether resins, polyphenylene sulfide resins, and phenolic resins. In particular, AS resin, BAAS resin, and thermoplastic polyurethane resin are preferred for improving fluidity, ABS resin and thermoplastic polyurethane resin are preferred for improving impact resistance, and polyester resin is preferred for improving chemical resistance. Furthermore, polyphenylene ether resins, polyphenylene sulfide resins, phenol resins, and the like are expected to have the effect of improving flame retardancy. These resins may be used alone or in combination of two or more kinds.

[0051] When other resins are used, in order to maintain good total light transmittance and weather resistance, the amount is preferably more than 0 mass% and not more than 30 mass%, more preferably not more than 20 mass%, and even more preferably not more than 10 mass%, relative to 100 mass% of the methacrylic resin composition.

[0052] Examples of the other additives include, but are not limited to, plasticizers such as phthalate esters, fatty acid esters, trimellitate esters, phosphate esters, and polyesters; release agents such as higher fatty acids, higher fatty acid esters, and higher fatty acid mono-, di-, or triglycerides; antistatic agents such as polyethers, polyether esters, polyether ester amides, alkyl sulfonates, and alkylbenzene sulfonates, and stabilizers such as light stabilizers; lubricants, flame retardant assistants, conductivity imparting agents, stress relaxation agents, crystallization accelerators, hydrolysis inhibitors, strength modifiers, sliding property improvers, compatibilizers, nucleating agents, reinforcing agents, reinforcing agents, flow adjusters, sensitizers, thickeners, anti-settling agents, anti-sagging agents, fillers, defoamers, coupling agents, rust inhibitors, antibacterial and anti-fungal agents, antifouling agents, conductive polymers, and the like.

[0053] In the methacrylic resin composition of the present embodiment, the content of the other additives relative to 100% by mass of the methacrylic resin composition is preferably 0.03% by mass or more, more preferably 0.05% by mass or more, in order to improve releasability when a release agent is used. In order to prevent molding defects such as bleed-out, the content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less. In order to effectively modify the strength when a strength modifier is used, the content is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more. In order to ensure good heat deformation resistance and flowability, the content is preferably 35% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less. By containing them in the above numerical ranges, the functions of each material can be exhibited.

[0054] <Method for producing methacrylic resin composition> The methacrylic resin composition of the present embodiment can be produced, for example, by mixing the above-mentioned methacrylic resin with, optionally, the above-mentioned ultraviolet absorber, the above-mentioned dye / pigment, and the above-mentioned other additives. The mixing method is not particularly limited, but may be a melt kneading method, a solvent kneading method, a dry blending method, or the like. From the viewpoint of productivity, the melt kneading method and the dry blending method are preferred. The equipment used for mixing may be a typical kneader or mixer, and specific examples include a single-screw extruder, a twin-screw extruder, a variable shell mixer, a Banbury mixer, and a tumbler. As a method of melt kneading, it is preferable to use a twin-screw extruder, since additives such as dyes and pigments can be uniformly dispersed and the resulting resin molded article can have a good uniformity in color tone.

[0055] In the case of melt kneading, the production temperature is preferably 200° C. or higher and 320° C. or lower. From the viewpoint of productivity, it is more preferably 210° C. or higher, and even more preferably 220° C. or higher, and from the viewpoint of preventing yellowing of the methacrylic resin composition due to decomposition of the resin, it is more preferably 290° C. or lower, and even more preferably 280° C. or lower.

[0056] -Vicat softening temperature of methacrylic resin composition- The methacrylic resin composition of the present embodiment has a Vicat softening temperature of 104° C. or higher according to ISO 306 B50. When the methacrylic resin composition of the present embodiment has a Vicat softening temperature of 104° C. or higher, the composition has sufficient heat distortion resistance even when used outdoors under direct sunlight or when an internal light source is used. In particular, the composition can be suitably used in applications requiring high heat distortion resistance, such as vehicle lighting components, which are exposed to direct sunlight for long periods of time and use an internal light source. The Vicat softening temperature is more preferably 106°C or higher, and further preferably 108°C or higher. The Vicat softening temperature is 140° C. or less, preferably 135° C. or less, more preferably 130° C. or less, and even more preferably 120° C. or less, in order to achieve a good balance between rigidity and mechanical strength. The Vicat softening temperature can be adjusted by adjusting the molecular weight and monomer composition of the methacrylic resin and the content of additives. More specifically, the Vicat softening temperature can be measured by the method described in the Examples below.

[0057] -Shear viscosity of methacrylic resin composition- The methacrylic resin composition of this embodiment has a shear viscosity of 1800 Pascal-seconds to 5000 Pascal-seconds when tested in a rotational rheometer in an oscillation frequency sweep test mode, using a cone-plate jig, with a gap of 0.05 mm, a strain of 10%, under a nitrogen flow, at a test temperature of 260°C, and at an angular velocity of 1 rad / second. By having a shear viscosity of 1800 Pascal-seconds or more, when the methacrylic resin composition is in contact with another thermoplastic resin composition in a molten state in a multicolor molded product, even if the outermost surface melts due to thermal welding, if it is colored, the shear viscosity in the molten state is high and diffusion to the other methacrylic resin composition in the molten state is suppressed, and color transfer is suppressed, resulting in good resistance to color transfer. From the viewpoint of suppressing color migration, the shear viscosity is preferably 1900 Pascal seconds or more, more preferably 2000 Pascal seconds or more, and even more preferably 2100 Pascal seconds or more. In order to improve molding processability, particularly in injection molding, the shear viscosity is 5000 Pascal seconds or less, preferably 4500 Pascal seconds or less, more preferably 4000 Pascal seconds or less, and even more preferably 3500 Pascal seconds or less, so that a holding pressure acts effectively and molding defects such as sink marks are prevented.

[0058] The methacrylic resin composition of the present embodiment has a shear viscosity of 300 Pascal seconds or more, preferably 400 Pascal seconds or more, more preferably 500 Pascal seconds or more, and even more preferably 600 Pascal seconds or more, in order to prevent molding defects such as silver streaks caused by molding gas, measured in a rotational rheometer in an oscillation frequency sweep test mode, using a cone plate jig, with a gap of 0.05 mm, a strain of 10%, under nitrogen flow, at a test temperature of 260 ° C., and at an angular velocity of 100 rad / sec, which is an index of fluidity during molding processing. In addition, the shear viscosity is 1000 Pascal seconds or less, preferably 800 Pascal seconds or less, more preferably 770 Pascal seconds or less, and even more preferably 750 Pascal seconds or less, so that a multi-color molded product having a small area rib-type welded part can be molded well to show good molding fluidity and to express high designability.

[0059] -Mid-point glass transition temperature measured using a differential scanning calorimeter- The methacrylic resin composition of the present embodiment preferably has a midpoint glass transition temperature (°C) of 111°C or higher, as determined from a glass transition curve obtained by heating from 40°C to 210°C at a heating rate of 10°C / min in a nitrogen gas atmosphere using a differential scanning calorimeter (DSC) and α-alumina as a reference in accordance with JIS K7121. The midpoint glass transition temperature (°C) obtained by the measurement method shown in the examples described later not only indicates that the higher the value, the better the heat distortion resistance of the resin composition, but also indicates the temperature at which the glass state transitions to a solid state, and the higher the value, the shorter the time from the molding temperature to solidification, which is effective in suppressing color migration and exhibiting good color migration resistance when forming a multi-color molded product. The midpoint glass transition temperature of the above methacrylic resin composition is preferably 109°C or higher, more preferably 111°C or higher, even more preferably 112°C or higher, and particularly preferably 113°C or higher. In addition, in order to achieve a good balance between the strength and fluidity of the methacrylic resin composition, the midpoint glass transition temperature is preferably 143°C or lower, more preferably 135°C or lower, even more preferably 130°C or lower, and particularly preferably 125°C or lower.

[0060] [Molded body] The molded article of the present embodiment includes the methacrylic resin composition of the present embodiment described above, and may be a molded article consisting of only the methacrylic resin composition of the present embodiment described above. For example, it is a molded article obtained by molding the methacrylic resin composition of the present embodiment described above. Among them, the molded article of the present embodiment is preferably an injection molded article obtained by injection molding.

[0061] Examples of methods for obtaining a molded body include known molding methods such as injection molding, extrusion molding, and pressure molding, and the obtained molded body may be subjected to secondary molding using known molding methods such as pressure molding and vacuum molding.

[0062] In the case of injection molding, the molding temperature is preferably 200° C. or higher and 320° C. or lower. From the viewpoint of productivity, the temperature is more preferably 210° C. or higher, and even more preferably 220° C. or higher, and from the viewpoint of preventing yellowing of the methacrylic resin composition due to decomposition of the resin, the temperature is more preferably 290° C. or lower, and even more preferably 280° C. or lower.

[0063] <Multicolor molded object> The multicolor molded article of the present embodiment includes the methacrylic resin composition of the present embodiment described above, and may be a molded article consisting of only the methacrylic resin composition of the present embodiment described above. For example, it is a multicolor molded article obtained by molding the methacrylic resin composition of the present embodiment described above. Among them, the multicolor molded article of the present embodiment is preferably a multicolor injection molded article obtained by injection molding. The multi-color molded body of this embodiment may be a two-color molded body, a three-color molded body, or a four or more color multi-color molded body, but from the viewpoint of productivity, a two-color molded body or a three-color molded body is preferable. At this time, from the viewpoint of design, each of the methacrylic resin composition molded articles is at least partially heat-welded, rather than being mechanically joined by a snap-fit ​​structure or the like.

[0064] (Configuration of multi-color molded body) In order that the colors of the respective molded bodies are clearly distinguishable from one another and that the multi-color molded body of this embodiment exhibits high designability, it is preferable that the molded body A made of a methacrylic resin composition having a total light transmittance of 80% or more and the molded body B made of a methacrylic resin composition having a total light transmittance of 50% or less are contained, and it is more preferable that the molded body consist only of the molded body A made of a methacrylic resin composition having a total light transmittance of 80% or more and the molded body B made of a methacrylic resin composition having a total light transmittance of 50% or less.

[0065] The greater the difference in total light transmittance, the more aesthetically pleasing the multicolor molded body will be. Therefore, the total light transmittance of the methacrylic resin composition molded body A having a total light transmittance of 80% or more is preferably 85% or more, and even more preferably 90% or more. The total light transmittance of the methacrylic resin composition molded product B having a total light transmittance of 50% or less is more preferably 40% or less, further preferably 30% or less, and may be 0%. The total light transmittance of a molded product is a value measured by cutting out a part of a multicolor molded product that is as smooth as possible and free of gate marks, parting lines, prisms, etc., and measuring it using a haze meter or the like in accordance with a measurement method conforming to JIS K7361. If it is not possible to cut out a measurement sample that is free of gate marks, parting lines, prisms, etc., a value measured using a measurement sample that includes gate marks, parting lines, prisms, etc. in as small an area as possible may be used.

[0066] The multi-color molded article of the present embodiment preferably contains, in at least one color as a molded article made of a methacrylic resin composition constituting the multi-color molded article, a methacrylic resin composition for multi-color molding, which has a shear viscosity of 1800 Pascal-seconds or more and 5000 Pascal-seconds or less at an angular velocity of 1 rad / second, and a shear viscosity of 300 Pascal-seconds or more and 1000 Pascal-seconds or less at an angular velocity of 100 rad / second, as measured using a rotational rheometer in an oscillation frequency sweep test mode using a cone-plate jig, with a gap of 0.05 mm, a strain of 10%, and under a nitrogen flow, at 260°C., and a Vicat softening temperature of 104°C or more (preferably 104°C or more and 140°C or less) as measured in accordance with ISO 306 B50.In the present embodiment, either a molded product A made of a methacrylic resin composition having a total light transmittance of 80% or more or a molded product B made of a methacrylic resin composition having a total light transmittance of 50% or less is measured using a rotational rheometer in an oscillation frequency sweep test mode, with a cone-plate fixture, a gap of 0.05 mm, a strain of 10%, under a nitrogen gas flow, at 260°C, a shear viscosity at an angular velocity of 1 rad / sec of 1800 Pascal-seconds or more and 5000 Pascal-seconds or less, a shear viscosity at an angular velocity of 100 rad / sec of 300 Pascal-seconds or more and 1000 Pascal-seconds or less, and a shear viscosity at an angular velocity of 100 rad / sec of 200 Pascal-seconds or more and 200 Pascal-seconds or less. The multicolor molded article of this embodiment is preferably obtained by molding a methacrylic resin composition for multicolor molding having a Vicat softening temperature of 104°C or higher (preferably 104°C or higher and 140°C or lower) measured in accordance with ISO 306 B50. The multicolor molded article of this embodiment is obtained by molding a methacrylic resin composition molded article A having a total light transmittance of 80% or higher and a methacrylic resin composition molded article B having a total light transmittance of at least 50%. The multicolor molded article is preferably obtained by molding a methacrylic resin composition molded article A having a total light transmittance of 80% or higher and a methacrylic resin composition molded article B having a total light transmittance of at least 50%. The multicolor molded article of this embodiment is ... It is more preferable that the multicolor molding is formed by molding a methacrylic resin composition for multicolor molding having a Vicat softening temperature of 104 ° C. or higher (preferably 104 ° C. or higher and 140 ° C. or lower) measured in accordance with ISO 306 B50, and it is even more preferable that all of the constituent molded bodies of the multicolor molding are formed by molding a methacrylic resin composition for multicolor molding having a shear viscosity of 1800 Pascal seconds or higher and 5000 Pascal seconds or lower at an angular velocity of 1 rad / sec using a rotational rheometer in an oscillation frequency sweep test mode, a cone plate jig, a gap of 0.05 mm, a strain of 10%, a nitrogen flow, 260 ° C., and a shear viscosity of 300 Pascal seconds or higher and 1000 Pascal seconds or lower at an angular velocity of 100 rad / sec, and a Vicat softening temperature of 104 ° C. or higher (preferably 104 ° C. or higher and 140 ° C. or lower) measured in accordance with ISO 306 B50.

[0067] (Thickness t of the constituent molded body of the multi-color molded body) In the multicolor molded product of this embodiment, the thickness t of each of the molded products of the respective colors is preferably 0.6 mm or more, more preferably 1 mm or more, and even more preferably 1.2 mm or more in order to obtain a molded product having sufficient strength for practical use as a molded product made of a methacrylic resin composition. In addition, in order to obtain a molded product having a good appearance with few molding defects such as sink marks, the thickness t is preferably 8 mm or less, more preferably 5 mm or less, and even more preferably 4 mm or less. The thicknesses of the molded products of the respective colors may be the same or different. The thickness t of the molded body refers to the thinnest part in the distance from one surface of the multi-colored molded body to the other surface (for example, from one design surface to the other design surface when both surfaces are designed), excluding ribs, gate marks, prisms, heat-sealed parts with methacrylic resin molded bodies, and heat-sealed parts with resin molded bodies that are not methacrylic resin molded bodies. When one of the molded bodies of each color covers the other, the thickness t of each molded body is the distance from one surface to the other surface to the point where the color changes with the naked eye, and the distance from the point where the color changes with the naked eye to the surface that faces the design surface.

[0068] (Heat-welded parts of multi-color molded bodies) The multicolor molded product of the present embodiment preferably has at least a heat-welded portion between molded products of different colors. In particular, it is preferable that the molded product A made of a methacrylic resin composition and the molded product B made of a methacrylic resin composition are at least partially heat-welded. In order to exhibit better color transfer resistance, the heat-welded portion between the molded product A made of a methacrylic resin composition and the molded product B made of a methacrylic resin composition is preferably 60% or less, more preferably 50% or less, and even more preferably 40% or less of the surface area of ​​the design surface of the multicolor molded product. In order to exhibit good strength as a multicolor molded product, it is preferably more than 0%, more preferably 2% or more, even more preferably 4% or more, and particularly preferably 6% or more. The multicolor molded body of this embodiment preferably has a design surface on its surface. For example, when a plurality of molded bodies are stacked in a line in the surface direction (FIG. 1), the design surface is preferably on only one surface, and may be on both surfaces. When a plurality of molded bodies are stacked in the thickness direction, the design surface may be on only one surface, or may be on both surfaces. Here, the design surface refers to a portion on the surface of the multicolor molded body that is intentionally designed. In the case of a molded body made of a methacrylic resin composition, it is preferable that the design is for effectively scattering light or for finishing the surface to a glossy mirror surface. The design surface can be confirmed by visually inspecting the surface of the multicolor molded body. The area ratio of the design surface is preferably 10 to 100%, more preferably 30 to 100%, and even more preferably 100%, relative to 100% of one surface area of ​​the multicolor molded article. The areas of the design surfaces on each surface may be the same or different. The surface area of ​​the design surface of the multicolor molded article may be the surface area of ​​the design surface that has the largest surface area among the design surfaces of any of the surfaces of the multicolor molded article. When multiple molded bodies are stacked in a line in the plane direction (FIG. 1), the heat-sealed portion may be formed in the thickness direction. When multiple molded bodies are stacked in the thickness direction, the heat-sealed portion may be formed in the plane direction perpendicular to the thickness direction. The heat-sealed portion can be visually confirmed by observing the multicolored molded body from the side of the molded body A made of a methacrylic resin composition having a total light transmittance of 80% or more, whether the multiple molded bodies are stacked in a line in the surface direction (FIG. 1) or stacked in the thickness direction, and its area can be calculated from the dimensions measured using an image dimension measuring device or a laser sensor. If the multicolored molded body is surrounded by colored members and the heat-sealed portion cannot be visually confirmed from the outside, the colored members can be removed to leave only the molded body having a total light transmittance of 80% or more and the molded body having a total light transmittance of 50% or less, and the multicolored molded body can be visually confirmed from the side of the molded body A having a total light transmittance of 80% or more.

[0069] In order to obtain a multicolor molded product with good strength of the heat-sealed parts, the width w of each heat-sealed part is preferably greater than 1, more preferably 1.2 or more, and even more preferably 1.8 or more, with respect to the thickness t of each color molded product, w / t. In order to obtain good design of the multicolor molded product, it is preferably 7 or less, more preferably 6 or less, and even more preferably 5 or less. Here, the width w of the heat-sealed part refers to the length of the shortest side of the sides formed by the heat-sealed parts when multiple molded products are aligned and stacked in the surface direction (FIG. 1), and the same applies when multiple molded products are stacked in the thickness direction. When multiple molded products are stacked in the thickness direction, the length of the shortest side of the sides formed by the heat-sealed parts may be the length of the shortest side of the molded product with the smaller internal area. In addition, the thickness t of each color molded product refers to the average value of the distance between the measurable surfaces of two molded products made of a methacrylic resin composition to be heat-sealed, excluding the mechanism and the attachment parts to other members.

[0070] (Application) The multicolor molded article of the present embodiment has high designability and excellent heat deformation resistance, color transfer resistance, and moldability, and can therefore be suitably used for vehicle components, electrical and electronic components, lighting components, etc. Specifically, it is suitable for use as, for example, vehicle console panels, lighting covers and signs, vehicle lighting components, emblems, switch panels, call buttons, plastic model parts, condiment containers, etc. In particular, it is suitable for use as vehicle lighting components and combination lamps (particularly, rear combination lamps). EXAMPLES

[0071] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.

[0072] [Raw materials] (Methacrylic resin) The raw materials of the methacrylic resin used in the production of the methacrylic resin composition are as follows. Methyl methacrylate (MMA): Asahi Kasei (containing 2.5 ppm of 2,4-dimethyl-6-t-butylphenol manufactured by Chugai Boeki as a polymerization inhibitor) Methyl acrylate (MA): Manufactured by Mitsubishi Chemical (containing 14 ppm of 4-methoxyphenol manufactured by Kawaguchi Chemical Industry Co., Ltd. as a polymerization inhibitor) Ethyl acrylate (EA): manufactured by Mitsubishi Chemical Cyclohexylmaleimide (CMI): Nippon Shokubai n-Octyl mercaptan: Arkema 2-Ethylhexyl thioglycolate: manufactured by Tokyo Chemical Industry Co., Ltd. Lauroyl peroxide: Made by Nippon Oil & Fats - Tribasic calcium phosphate: Manufactured by Nippon Chemical Industry Co., Ltd., used as a suspending agent Calcium carbonate: Shiraishi Kogyo Co., Ltd., used as a suspending agent Sodium lauryl sulfate: Manufactured by Wako Pure Chemical Industries, used as a suspension aid (UV absorber) Tinuvin P: BASF Benzotriazole UV absorber Melting point 128℃ (lubricant) Kalcol 8098: Kao Chemical (dye) Dye 1: Macrolex Red EG: LANXESS (Perinone dye with melting point of 318°C) Dye 2: Macrolex Violet 3R: LANXESS (anthraquinone dye with a melting point of 213°C) Dye 3: Plast Red 8350: Arimoto Chemical (anthraquinone dye with a melting point of 138°C) Dye 4: Sumiplast Green G: Sumika Chemtex (anthraquinone dye with a melting point of 217°C) Dye 5: Plast Blue 8520: Arimoto Chemical (anthraquinone dye with a melting point of 230°C) (Pigments) Pigment 1: Mitsubishi Carbon Black #2600: manufactured by Mitsubishi Chemical

[0073] [Measurement and evaluation method] (Measurement of molecular weight of methacrylic resin in methacrylic resin composition) The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) (Mn is number average molecular weight) of the methacrylic resin were measured using the following device and conditions. Measurement equipment: Tosoh Corporation gel permeation chromatography (HLC-8320GPC) Measurement conditions: Columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were used, connected in series. With this column, high molecular weight molecules elute early, and low molecular weight molecules elute slowly. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Column temperature: 40℃ Sample: 0.02 g of methacrylic resin in 20 mL of tetrahydrofuran Injection volume: 10μL Developing solvent: tetrahydrofuran, flow rate: 0.6 mL / min, 2,6-di-t-butyl-4-methylphenol (BHT) was added at 0.1 g / L as an internal standard. As standard samples for the calibration curve, the following ten types of polymethyl methacrylate (PMMA Calibration Kit MM-10, manufactured by Polymer Laboratories) with known monodisperse peak molecular weights and different molecular weights were used. In addition, since the polymethyl methacrylates of the standard specimens used for the standard samples for the calibration curve each had a single peak, the corresponding peaks were expressed as weight peak molecular weights Mp, which was distinguished from the peak top molecular weights calculated when a sample had multiple peaks. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard material 10 850 Under the above conditions, the RI detection intensity was measured versus the elution time of the methacrylic resin. Based on the area in the GPC elution curve and the calibration curve of a third-order approximation formula, the weight average molecular weight (Mw), molecular weight distribution (Mw / Mn), and the amount of molecular weight components present that is 1 / 5 or less of the peak top molecular weight (Mp) of the methacrylic resin were determined. Note that Mw is the value in Table 1 multiplied by 10,000.

[0074] (Analysis of structural units of methacrylic resins) 1 The monomer units were identified by H-NMR measurement, and their abundance (mass %) was calculated. 1 The measurement conditions for H-NMR measurement are as follows. Equipment: JEOL-ECA500 Solvent: CDCl3-d1 (deuterated chloroform) Sample: 1 g of methacrylic resin was dissolved in 10 ml of acetone, 20 ml of methanol was added dropwise, and the mixture was filtered. The insoluble matter was vacuum dried at 40°C for 15 hours, and 15 mg of the insoluble matter was dissolved in 0.75 mL of CDCl3-d1 to prepare a sample for measurement.

[0075] (Total light transmittance) The total light transmittance of the molded article was measured in accordance with JIS K 7361 using Nippon Denshoku's NDH 7000. The samples used were cut out from multicolor molded articles produced by injection molding, which will be described later.

[0076] (Evaluation of color transfer resistance) The occurrence of color transfer due to remelt in the heat-sealed portion of the multicolor molded body shown in Fig. 1 was evaluated using the multicolor molded body for evaluation. The heat-sealed portion was clearly lined and no color transfer was observed, and was rated as ⊚ (excellent). The portion where the line fluctuation between the colors due to remelt and color transfer of 0.5 mm or less was observed was rated as ◯ (good). The portion where the line fluctuation between the colors due to remelt and color transfer of more than 0.5 mm and 1 mm or less was observed was △ (sufficient for practical use). The portion where the obvious color transfer of more than 1 mm was observed was × (bad). In Example 17, the evaluation was performed in the same manner as above using the multicolor molded body for evaluation 2.

[0077] <Evaluation of heat deformation resistance> Dumbbell test pieces molded using the resin pellets obtained in the Examples and Comparative Examples described below were used to measure the VICAT softening temperature (°C) in accordance with ISO 306 B50, and used as an index for evaluating heat distortion resistance. Except for the methacrylic resin composition, the dumbbell test pieces were annealed at 83°C for 16 hours and then cooled in a desiccator at 23°C for 1 hour. For the methacrylic resin composition, the dumbbell test pieces were annealed at 75°C for 16 hours and then cooled in a desiccator at 23°C for 1 hour. If the VICAT softening temperature was 108°C or higher, it was rated as "◎" (excellent); if it was 106°C or higher but less than 108°C, it was rated as "〇" (good); if it was 104°C or higher but less than 106°C, it was rated as "△" (sufficient for practical use); and if it was less than 104°C, it was rated as "×" (poor).

[0078] (Shear Viscosity Measurement) Methacrylic resin composition pellets dried at 80°C for 18 hours were press molded to a thickness of 1 mm to prepare samples. As indicators of moldability and color transfer resistance, a cone-plate jig was used with a rotational rheometer, with a gap of 0.05 mm and strain of 10%, and the shear viscosity (shear viscosity A) at 260°C and an angular velocity of 1 rad / sec and the shear viscosity (shear viscosity B) at an angular velocity of 100 rad / sec were measured in a nitrogen gas flow using a TA Instruments viscoelasticity measuring device ARES-G2 in an oscillation frequency sweep test mode, and the measured values ​​were rounded off to the third digit from the top.

[0079] (midpoint glass transition temperature) As an index of heat deformation resistance, the midpoint glass transition temperature of a methacrylic resin composition sample cut out from a multicolor molded body was measured. Using a differential scanning calorimeter (Diamond DSC manufactured by PerkinElmer Japan Co., Ltd.), in a nitrogen gas atmosphere, α-alumina was used as a reference, and in accordance with JIS-K-7121, about 10 mg of the sample was heated from 40 ° C. to 210 ° C. at a heating rate of 10 ° C. / min, then cooled to 40 ° C., and heated again from 40 ° C. to 210 ° C. at a heating rate of 10 ° C. / min, and the midpoint glass transition temperature was obtained from the second DSC curve. The midpoint glass transition temperature was rated as ◎ (particularly excellent) at 113 ° C. or higher, ◯ (good) at 112 ° C. or higher and less than 113 ° C., △ (no practical problem) at 109 ° C. or higher and less than 112 ° C., and × (bad) at less than 109 ° C. In addition, when multiple inflection points were observed in the glass transition curve, the value of the largest inflection point was adopted. The midpoint glass transition temperature of the methacrylic resin can also be measured in the same manner as above.

[0080] <Molding of dumbbell test specimens> (injection molding) The pellets of the obtained methacrylic resin composition were put into an injection molding machine (Shibaura Machine EC-100SX) to mold a type 1A dumbbell test piece as a sample for evaluation. The molding conditions were in accordance with ISO8257-2. The filling speed was 10 cm 3 / second.

[0081] <Methacrylic resin> As the methacrylic resins, methacrylic resins 1 to 5 produced in the following Production Examples 1 to 5 were used.

[0082] (Production Example 1 (Production of Methacrylic Resin 1)) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of ion-exchanged water was added to a 60 L reactor, and the temperature was raised to 80° C., and then mixed liquid (a), 21.2 kg of methyl methacrylate, 0.65 kg of methyl acrylate, 27 g of lauroyl peroxide, and 62 g of n-octyl mercaptan were added. Thereafter, polymerization was carried out for 1 hour at an initial polymerization temperature of about 60°C, then the temperature was raised to about 80°C, and suspension polymerization was carried out while maintaining the temperature at about 80°C. After an exothermic peak was observed, the temperature was raised to 92°C at a rate of 1°C / min, and the mixture was aged for 60 minutes, at which point the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated and dried to obtain polymer microparticles 1 (methacrylic resin 1).

[0083] <Production Example 2 (Production of Methacrylic Resin 2)> Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid. Next, 23 kg of ion-exchanged water was added to a 60 L reactor and the temperature was raised to 80° C., and the entire mixed liquid, 4.95 kg of methyl methacrylate, 0.1 kg of methyl acrylate, 36 g of lauroyl peroxide, and 100 g of 2-ethylhexyl thioglycolate were added. Then, the suspension polymerization was carried out while maintaining the temperature at about 80°C, and after observing the exothermic peak, the temperature was raised to 92°C at a rate of 1°C / min, and the temperature was maintained at 92°C to 94°C for 30 minutes. After that, the temperature was lowered to 80°C at a rate of 1°C / min, and then 15.0 kg of methyl methacrylate, 0.4 kg of methyl acrylate, 19 g of lauroyl peroxide, and 28 g of n-octyl mercaptan were added, and the suspension polymerization was continued while maintaining the temperature at about 80°C. After observing the exothermic peak, the temperature was raised to 92° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes to essentially complete the polymerization reaction. Next, the mixture was cooled to 50°C and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated and dried to obtain polymer microparticles 2 (methacrylic resin 2).

[0084] <Production Example 3 (Production of Methacrylic Resin 3)> Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid. Next, 26 kg of ion-exchanged water was added to a 60 L reactor and the temperature was raised to 80° C., and the entire mixed liquid, 3.76 kg of methyl methacrylate, 0.1 kg of ethyl acrylate, 27 g of lauroyl peroxide, and 62 g of 2-ethylhexyl thioglycolate were added. Then, the suspension polymerization was carried out while maintaining the temperature at about 80°C, and after observing the exothermic peak, the temperature was raised to 92°C at a rate of 1°C / min, and the temperature was maintained at 92°C to 94°C for 30 minutes. After that, the temperature was lowered to 80°C at a rate of 1°C / min, and then 17.0 kg of methyl methacrylate, 1.35 kg of ethyl acrylate, 23 g of lauroyl peroxide, and 35 g of n-octyl mercaptan were added, and the suspension polymerization was continued while maintaining the temperature at about 80°C. After observing the exothermic peak, the temperature was raised to 92° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes to essentially complete the polymerization reaction. Next, the mixture was cooled to 50°C and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated and dried to obtain polymer microparticles 3 (methacrylic resin 3).

[0085] <Production Example 4 (Production of Methacrylic Resin 4)> Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid. Next, 26 kg of ion-exchanged water was added to a 60 L reactor and the temperature was raised to 80° C., and the entire mixture, 20.5 kg of methyl methacrylate, 1.32 kg of methyl acrylate, 33 g of lauroyl peroxide, and 28.5 g of n-octyl mercaptan were added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80°C, and after observing an exothermic peak, the temperature was increased to 92°C at a rate of 1°C / min. Thereafter, the mixture was aged for 60 minutes to essentially complete the polymerization reaction. Next, the mixture was cooled to 50°C and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated and dried to obtain polymer microparticles 4 (methacrylic resin 4).

[0086] <Production Example 5 (Production of Methacrylic Resin 5)> Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid. Next, 23 kg of ion-exchanged water was put into a 60 L reactor, and the temperature was raised to 80° C., and the entire mixed liquid, 5.5 kg of methyl methacrylate, 40 g of lauroyl peroxide, and 90 g of 2-ethylhexyl thioglycolate were then put into the reactor. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80° C. An exothermic peak was observed 80 minutes after the raw materials were added. Next, the temperature was raised to 92°C at a rate of 1°C / min, and then the temperature was maintained at 92°C to 94°C for 30 minutes. After that, the temperature was lowered to 80°C at a rate of 1°C / min, and then 16.2 kg of methyl methacrylate, 0.75 kg of ethyl acrylate, 17 g of lauroyl peroxide, and 20 g of n-octyl mercaptan were added, and the suspension polymerization was continued while maintaining the temperature at about 80°C. An exothermic peak was observed 105 minutes after the raw materials were added. Thereafter, the temperature was raised to 92° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes to essentially complete the polymerization reaction. Next, the mixture was cooled to 50°C and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated and dried to obtain polymer microparticles 5 (methacrylic resin 5).

[0087] [Methacrylic resin composition for multi-color molding] Examples 1 to 6, Comparative Examples 1 to 7 Additives such as ultraviolet absorbers, dyes and pigments, and lubricants were added to methacrylic resins 1 to 3 and 5 in the proportions shown in Table 1, and the resins were melt-kneaded at 240°C in a φ26mm twin-screw extruder, and the strands were cooled and cut to produce resin pellets (methacrylic resin compositions). Methacrylic resin 4 was melt-kneaded at 260°C in a φ26mm twin-screw extruder to produce resin pellets (methacrylic resin compositions). Furthermore, the properties of each methacrylic resin composition were evaluated, and the results are shown in Table 1. In addition, the constituent monomer units of the methacrylic resin 1 in the methacrylic resin composition were MMA / MA=97 / 3% by mass. The constituent monomer units of the methacrylic resin 2 were MMA / MA=98.1 / 1.9% by mass. The constituent monomer units of the methacrylic resin 3 were MMA / EA=93.5 / 6.5% by mass. The constituent monomer units of the methacrylic resin 4 were MMA / MA=94 / 6% by mass. The constituent monomer units of the methacrylic resin 5 were MMA / EA=96.5 / 3.5% by mass.

[0088] [Table 1]

[0089] [Multicolor molded object] Examples 7 to 16, Comparative Examples 8 to 11 The multicolor molded products produced by the manufacturing method described below were evaluated for total light transmittance and color transfer resistance. The results are shown in Table 2.

[0090] [Manufacturing method 1 for multi-color injection molded products] (Injection molding) The methacrylic resin composition was fed into a multi-color injection molding machine to mold a multi-color injection molded body (primary injection side molded body: width 70 mm x length 120 mm, with a 9 mm high rib attached to the long side of the 120 mm long flow end, thickness t was 3 mm on the 70 mm x 120 mm surface, and the rib was also 3 mm thick. Secondary injection side molded body: same dimensions and paired shape as the primary injection side molded body, the rib was used as the heat-welded part) to produce the multi-color molded body for evaluation (Figure 1). The gate was installed at one side gate in the center of the 120 mm length of the primary injection molded body and the secondary injection molded body. 2 The dimensions of the mirror-finished design part of the 16,800 mm2 mirror-finished design were calculated using a Keyence IM-8000 dimension measuring instrument. 2 The ratio of the area of ​​the heat-welded portion to the surface area of ​​the design surface (100%) was 6.4%, and the w / t was 3. The mold used had both the cavity and core sides polished with a grit of #8000 to create a mirror finish. The molding conditions were as follows: Injection molding machine: Sumitomo Heavy Industries SE-280D-CI (mold clamping force 280t, multi-color molding) Injection conditions Mold temperature: 70℃ Filling speed: 90mm / sec, pressure holding time: 12 seconds Cooling time: 30 seconds Molding cycle for each layer: 62 seconds Setting molding temperature: 270℃ [Manufacturing method 2 for multi-color injection molded products] (Injection molding) The methacrylic resin composition was fed into a multi-color injection molding machine, and a multi-color injection molded body (primary injection side molded body: width 70 mm x length 120 mm, thickness t was 2 mm on the 70 mm x 120 mm surface, secondary injection side molded body: width 70 mm x length 100 mm, thickness t was 2 mm on the 50 mm x 120 mm surface, laminated in the thickness direction so as to cover the primary injection side molded body) was molded into evaluation multi-color molded body 2. The gates were set at one side gate in the center of the 120 mm length of the primary injection molded body and the secondary injection molded body. 2) was calculated using a Keyence IM-8000 dimension measuring instrument, and the design surface area (8,400 mm 2 The ratio of the area of ​​the heat-welded portion to the surface area of ​​the design surface (100%) was 72.3%, and the w / t was 25. The mold used had both the cavity and core sides polished with a grit of #8000 to create a mirror finish. The molding conditions were as follows: Injection molding machine: Sumitomo Heavy Industries SE-280D-CI (mold clamping force 280t, multi-color molding) Injection conditions Mold temperature: 70℃ Filling speed: 70mm / sec, pressure holding time: 15 seconds Cooling time: 35 seconds Molding cycle for primary injection molding: 70 seconds Secondary injection molding cycle: 68 seconds Setting molding temperature: 270℃

[0091] [Table 2]

[0092] In Examples 1 to 6, methacrylic resin compositions for multicolor molding having shear viscosity A, shear viscosity B, and heat distortion resistance in ranges suitable for multicolor molding could be produced. When comparing the behavior of the multicolor molded products, Examples 1, 2, and 5 were particularly excellent, and Example 3 was good. Example 5 had a level of color transfer resistance sufficient for practical use when made into a multicolor molded product, but was slightly inferior compared to the other Examples. Example 6 had a level sufficient for practical use when made into a multicolor molded product, but the ribs, which are the heat-welded parts, had sink marks compared to the other Examples. In Comparative Examples 1 to 7, the shear viscosity A, shear viscosity B, and heat deformation resistance were not within the suitable range for multicolor molding.

[0093] In Examples 7 to 9 and Example 12, multicolor molded bodies having particularly excellent color transfer resistance were produced. In Examples 10, 13 to 15, multicolor molded bodies having good color transfer resistance were produced. In Examples 11 and 16, the color transfer resistance was at a practically sufficient level, but was slightly inferior to other Examples. In Example 17, a molded body was used in which the ratio of the area of ​​the heat-welded part to 100% of the surface area of ​​the design surface was 72.3% and the w / t was 25, so that the color transfer resistance due to remelt was at a practically sufficient level, but was slightly inferior to other Examples. In Comparative Example 8, only a methacrylic resin composition in which the shear viscosity A was not in the suitable range was used, so the color transfer resistance was not good. In Comparative Example 9, only a methacrylic resin composition in which the heat deformation resistance and the shear viscosity A were not in the suitable range was used, so the color transfer resistance was not good. In Comparative Example 10, a methacrylic resin composition having a heat distortion resistance and a shear viscosity A that were not within the preferred ranges and a methacrylic resin composition having shear viscosities A and B that were not within the preferred ranges were used, so the color transfer resistance was not good, and the ribs in the heat-sealed parts had large sink marks, resulting in a poor appearance of the molded product.In Comparative Example 11, a methacrylic resin composition having a shear viscosity A that was not within the preferred ranges and a methacrylic resin composition having a heat distortion resistance temperature and a shear viscosity A that were not within the preferred ranges were used, so the color transfer resistance was not good. [Industrial Applicability]

[0094] The multicolor molded article obtained by molding the methacrylic resin composition for multicolor molding of the present embodiment has high designability and excellent heat deformation resistance, color transfer resistance, moldability, and molded article appearance, and can be suitably used as vehicle parts, electrical and electronic parts, lighting parts, and miscellaneous goods. Specifically, it has industrial applicability as, for example, vehicle console panels, lighting covers and signs, vehicle lighting parts, emblems, switch panels, call buttons, plastic model parts, seasoning containers, etc., and in particular has industrial applicability as vehicle lighting parts and combination lamps (in particular, rear combination lamps).

Claims

1. Using a rotational rheometer, the oscillation frequency sweep test mode was performed using a cone-plate jig, with a gap of 0.05 mm and a strain of 10%, under a nitrogen flow, at a test temperature of 260° C., with a shear viscosity of 1,800 Pascal seconds or more and 5,000 Pascal seconds or less at an angular velocity of 1 rad / sec, and a shear viscosity of 300 Pascal seconds or more and 1,000 Pascal seconds or less at an angular velocity of 100 rad / sec. The Vicat softening temperature measured in accordance with ISO 306 B50 is 104°C or higher and 140°C or lower. Methacrylic resin composition for multi-color molding.

2. 2. The methacrylic resin composition for multicolor molding according to claim 1, which has a midpoint glass transition temperature of 111° C. or higher.

3. A multicolor molded article comprising the methacrylic resin composition for multicolor molding according to claim 1.

4. A multi-color molded article having two or more colors made of a methacrylic resin composition, The molding comprises a methacrylic resin composition molded product A having a total light transmittance of 80% or more, and a colored methacrylic resin composition molded product B having a total light transmittance of 50% or less, the colored methacrylic resin composition for multicolor molding according to claim 1, The methacrylic resin composition molded body A and the methacrylic resin composition molded body B are at least partially heat-welded to each other. Multi-color moldings with two or more colors.

5. A multi-color molded article having two or more colors made of a methacrylic resin composition, The present invention comprises a methacrylic resin composition molded product A made of the methacrylic resin composition for multicolor molding according to claim 1 having a total light transmittance of 80% or more, and a colored methacrylic resin composition molded product B having a total light transmittance of 50% or less, The methacrylic resin composition molded body A and the methacrylic resin composition molded body B are at least partially heat-welded to each other. Multi-color moldings with two or more colors.

6. A multi-color molded article having two or more colors made of a methacrylic resin composition, The present invention comprises a methacrylic resin composition molded product A made of the methacrylic resin composition for multicolor molding according to claim 1 having a total light transmittance of 80% or more, and a colored methacrylic resin composition molded product B made of the colored methacrylic resin composition for multicolor molding according to claim 1 having a total light transmittance of 50% or less, The methacrylic resin composition molded body A and the methacrylic resin composition molded body B are at least partially heat-welded to each other. Multi-color moldings with two or more colors.

7. The multicolor molded article according to claim 4 or 5, wherein the molded article A made of the methacrylic resin composition and the molded article B made of the methacrylic resin composition are injection molded articles.

8. The multicolor molded product according to claim 4 or 5, wherein the heat-sealed portion accounts for more than 0% and not more than 60% of 100% of the surface area of ​​the design surface of the multicolor molded product.

Citation Information

Patent Citations

  • Two-color injection-molded article

    JP2019202537A

  • Two-color injection-molded article

    JP2019202538A